Dielectrophoresis-Based Selective Droplet Extraction Microfluidic Device for Single-Cell Analysis - Seito Shijo; Daiki Tanaka; Tetsushi Sekiguchi; Jun-ichi Ishihara; Hiroki Takahashi; Masashi Kobayashi; Shuichi Shoji (Micromachines, 2023)
We developed a microfluidic device that enables selective droplet extraction from multiple droplet-trapping pockets based on dielectrophoresis. The device consists of a main microchannel, five droplet-trapping pockets with side channels, and drive electrode pairs appropriately located around the trapping pockets. Agarose droplets capable of encapsulating biological samples were successfully trapped in the trapping pockets due to the difference in flow resistance between the main and side channels. Target droplets were selectively extracted from the pockets by the dielectrophoretic force generated between the electrodes under an applied voltage of 500 V. During their extraction from the trapping pockets, the droplets and their contents were exposed to an electric field for 400–800 ms. To evaluate whether the applied voltage could potentially damage the biological samples, the growth rates of Escherichia coli cells in the droplets, with and without a voltage applied, were compared. No significant difference in the growth rate was observed. The developed device enables the screening of encapsulated single cells and the selective extraction of target droplets.